Effects of road humps on traffic speed and noise in Putrajaya residential areas - Bachok, Khairun Sarah Radhiah; Ahmad Sofi, Siti Syazwani; Kadar Hamsa, Abdul Azeez; Mohamed, Mohd Zin; Ibrahim, Mansor (Universiti Tunku Abdul Rahman (UTAR), 2016)
As a traffic calming measure, the installation of road humps in residential areas has helped reduce the speeds of vehicles along residential roads. However, it is also widely seen that changes in speed regarding sudden deceleration and acceleration near the road humps have increased the noise level of the traffic in the residential areas. This paper discusses the effects of road humps, as a traffic calming measure, on the traffic speed and noise levels in a residential area. The study was conducted for two different sets of road humps in Putrajaya, Malaysia. The speeds of moving vehicles and noise levels were measured for a 12-hour period using radar guns and noise level meters at selected points. The sample size was determined using the systematic sampling technique based on the 12-hour traffic volume count conducted beforehand. The relationship between speed and noise levels at road humps are assessed together with the respective road and hump characteristics, with the finding that the impacts on noise levels were influenced by the rate of speed reductions, which is dependent on the road hump and road geometrics. Road humps were also found to not necessarily contribute to reduction in noise levels despite being effective in reducing vehicle speeds.